Sistem Penjualan Merchandise Berbasis Aplikasi Mobile - I Dewa Gede Partha Wijaya,; I Made Widiartha, (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2023)
The rapid growth of mobile technology has revolutionized various industries, including merchandise sales. This paper presents a study on the development of a mobile applicationbased merchandise sales system aimed at replacing manual recording reports by merchandisers and expanding the range of reportable data. By harnessing the capabilities of mobile devices, the research focuses on analyzing merchandisers' requirements and designing user-friendly interfaces. Through thorough testing and evaluation, the system showcases its reliability and functionality. This study contributes to the existing body of knowledge by offering valuable insights into the advantages and challenges of adopting mobile technology in merchandise sales.
Keywords: Mobile Application, Sales Report, SDLC, Flowchart, UML